An Exploring the Dynamics of Academic Procrastination Research Trends : - Muhammad Fikri Fauzi; Nadia Amalia (Journal of Education Counseling, 2026)
Academic procrastination is a frequent threat to the academic process. Unmanaged academic procrastination can potentially lead to stress and even lead to student failure in their learning process. This study focuses on the dynamics of research on academic procrastination from 2017 to 2026 using the Systematic Literature Review PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method sourced from the Dimensions AI database due to its ease of access and broad reach. The results show that the dynamics of research on 'academic procrastination' continued to increase from 2017 to 2026, indicating attention and interest in related aspects due to their relevance to contemporary issues. This study is also enriched with visualizations from VOS Viewer including network visualization, overlay visualization, and density visualization. Some information was obtained such as authors and journals active in related research such as Abilio Afonso Lourenco from the University of Minho, Portugal with 5 publications, 32 citations and a 6.40 mean citation value, while Frontiers in Psychology is a journal house that is active in publishing articles with related keywords with data of 5 publications, 209 citations and a 41.80 mean citation value. This study proves that the dynamics of research on academic procrastination continues to increase and can be a reference and stimulus for further research that is more focused and impactful.